Pengaruh Pendapatan Asli Daerah (PAD) dan Rata-Rata Lama Sekolah terhadap Pertumbuhan Ekonomi di Provinsi Jawa Barat Periode 2011-2020 - Khoerudin, Nanang; Roisiyatin (LEMBAGA PENELITIAN DAN PENGABDIAN PADA MASYARAKAT, 2024)
Reality not all regions are able to finance regional expenditure using Regional Original Income (PAD). The average length of schooling indicates the higher level of formal education achieved by the people of a region. The higher the average length of schooling means the higher the level of education undertaken. The data used in this study is secondary data in the form of panel data, which is a combination of time series data (2011-2020) and cross section data (27 regencies/cities in West Java Province). The analytical technique used in this study is panel data regression analysis with the help of software eviews 9 which was analyzed using the Fixed Effect Model (FEM) method. The results of this study indicate that the Regional Original Income (PAD) variable has a positive and significant effect on economic growth in West Java Province, because the probability value is less than 5% or 0.05, which is 0.0000. While the Average Length of School (RLS) has a positive and significant effect. on Economic Growth in West Java Province, which means that every increase in RLS will increase Economic Growth. With an R square value of 99.7209 %, it means that the diversity of the dependent variable can be explained by the independent variables. The conclusion is that the increase in PAD causes an increase in economic growth in West Java Province and an increase in the average length of schooling causes an increase in economic growth in West Java Province. The influence of Regional Original Income (PAD) and Average Years of Schooling (RLS) on Economic Growth shows that PAD and Average Years of Schooling together influence Economic Growth, with an F-statistic value of 0.000000